Astragalus saponins improves stroke by promoting the proliferation of neural stem cells through phosphorylation of Akt. (15th September 2021) - Wang, Yu; Liu, Xu; Hu, Tingdong; Li, Xin; Chen, Yuru; Xiao, Guangxu; Huang, Juyang; Chang, Yanxu; Zhu, Yan; Zhang, Han; Wang, Ying
Abstract: Ethnopharmacological relevance: As one of major components of Buyang Huanwu decoction, Astragali Radix is broadly used for stroke treatment. Astragalus saponins (AST), the main active compound from Astragali Radix has the potentials for neuroprotection and improving spatial memory without clear pharmacological mechanism. Aim of the study: The aim of this study was to investigate that pretreatment of AST is beneficial to protect against focal ischemic stroke in mouse model and its related underlying mechanism. Materials and methods: The neurological and motor function of MCAO mice were assessed by TTC staining and CatWalk gait analysis. The effect of AST on proliferation of NSCs was showed by the expression of Ki67 of MCAO mice and the number and size of primary neurospheres cultured from adult SVZ. The intersection of stroke-related targets, neurogenesis targets and drug-related targets were identified by the online website (https://www.omicstudio.cn/index ). Then GO functional annotation and KEGG pathway enrichment analysis were performed. Candidate target Akt was confirmed to increase proliferation of cultured NSCs from adult SVZ by CCK8 assay and Western blot. Results: We found that with the prolongation of administration time, AST improved neurological and motor function of MCAO mice, by promoting the proliferation of NSCs both in vivo and in vitro . Then, the primary network among drug, genes and biological pathway was established by using compound-target-disease & function-pathway analysis of astragalus membranaceus. PI3K/Akt which plays a key role in cell proliferation was among the top 10 most significant GO terms from above three aspects. Further analysis using cultured NSCs from adult SVZ confirmed that AST, astragaloside I (A1) and astragaloside III (A3) increased the proliferation of NSCs through targeting Akt. Conclusion: The present study elucidated that Astragalus saponins pretreatment could provide a protective effect on experimental stroke mainly by enhancing proliferation of NSCs through targeting Akt. The findings provided a basis for the development of novel strategies for the treatment of stroke. Graphical abstract: Image 1 Highlights: The pretreatment of astragalus saponins is beneficial to protect against focal ischemic stroke in MCAO mouse. Astragalus saponins was found to promote proliferation of NSCs not only in vitro but also in vivo. Astragalus saponins increase the proliferation of NSCs through phosphorylation of Akt.